The formation of the digital economy and the problems of improving legal regulation in the field of information security - Anatoly A. Malyuk; Andrey V. Morozov (Безопасность информационных технологий, 2019)
Legal regulation is one of the three pillars on which rests the field of information security of the individuals, society and the state. Not without reason, since 1992, these issues have received close attention at all levels of the Federal and regional authorities of the Russian Federation. A significant number of scientific publications of Russian authors such as I. L. Bachilo, A. A. Streltsov, Yu. M. Baturin, T. A. Polyakova, etc. are devoted to these issues. The key point in addressing these issues is a holistic concept of building legislation in the sphere of information security, taking into account the dynamic nature of changes in other pillars of the industry, namely, technology and human aspects (the formation a culture of information security in society). Thus, the concept of regulatory support should be linked to the information security policy as an essential element of the national security strategy of the state. This paper deals with the approaches to formation of such a concept. It consistently considers the problems of structuring the subject area of information security, the directions of legal regulation of activities in this area, the levels of appropriate legal support. In conclusion, the most acute problems to date that require urgent solutions are formulated.